Impact of the American Heart Association's Heart Health in the Young Curriculum on Cardiovascular Knowledge Scores and Behavior Changes in Smoking, Exercise, and Nutrition in Eighth Grade Students - Hebert, Fred (My University, 1987)
This was a pre-test post-test experimental study. The experimental group received 15 (45 minute) lessons from the AHA curriculum. Pre-test and post-test scores were recorded. The control group attended regular health education classes between the pre-test and the post-test. The Know Your Body Health Questionnaire for grades 6-8 was used as a base instrument to assess knowledge change. The Know Your Body Health Habits Survey instrument was used to assess behavior change in the areas of smoking and exercise. The DINE system, created by Darwin Dennison, was used to measure nutrition change. The data was analyzed using between group T-tests and Pearson product moment correlations. The alpha level was established at the .05 level of significance. Results indicated significant differences in knowledge change scores in the experimental group versus the control group. None of the 46 subjects in the study reported smoking behavior, makinq it impossible to test for smoking change. Statistical significance was not demonstrated in exercise behavior change in either group. There was not a statistically significant correlation demonstrated in either the experimental or the control group between knowledge change scores and change scores in exercise behavior. Interestingly, statistical significance was demonstrated in diet behavior in a negative direction. Both groups decreased their heart healthy nutritional behavior from pre-test to post-test. The experimental qroup also demonstrated a statistically significant correlation between knowledge change and diet change, illustrating decreased heart healthy diet with increased knowledge. This was not true in the control group. The study indicates the need for comprehensive long-term health education programs to bring about necessary changes in health habits and skills.
Keywords: Food habits - Health aspects; Junior high school students - Health and hygiene; Health education (Secondary) - Curricula; American Heart Association